Enthusiasm or uncertainty: small area variations in the use of mammography services in Ontario, Canada. Issue 4 (August 1997) - Goel, V; Iron, K; Williams, J I
Abstract : STUDY OBJECTIVE: To examine the variation in mammography utilisation in relation to age group and indication across health planning regions in Ontario, Canada. DESIGN: This study includes all women aged 30 and over in Ontario who received a mammogram between July 1, 1990 and December 31, 1991. Data from a sample of 10, 000 women aged 50-69 were used to assign mammogram indication as "screening", "possible diagnostic", or "probable diagnostic" based on previous health care utilisation patterns. Age specific rates and age adjusted rates in relation to age group (30-39, 40-49, 50-69, and 70 + years) and region were derived. MAIN RESULTS: Overall, 572, 762 women received one or more mammograms. Rates increased from 30-54 years and decreased thereafter. Similar variations were seen in the 40-49 and 50-69 age groups. The ranking in the area specific rates remained consistent for all ages except the 30-39 year range. In relation to indication, the largest variation across regions occurred in the screening group. CONCLUSIONS: Mammography utilisation varies across age groups. The greatest variability is for screening, probably because of physician referral patterns, patient uptake, and perhaps access to mammography. The extent of variation was similar when compared between groups where recommendations were consistent (ages 50-59) and where they were inconsistent (ages 40-49) suggesting that perhaps enthusiasm rather than uncertainty is related to regional variation for this procedure.